Potential fertilizer from sugarcane bagasse ash from sugar industries - Arias-Cedeño, Quirino; López-Sánchez, Raúl; Sainz-Rosales, Luis Ricardo; Verdecia-Casanova, María Virginia; Eichler-Löbermann, Bettina (Revista Cubana de Química, 2021)
The reuse of residues from agroindustrial processes is an ecological alternative that allows implementing nutrient cycling in agriculture and saving fertilizers; for this purpose the potential of the ashes generated by the combustion of sugarcane bagasse in the five sugar industries of the province of Granma was evaluated. The best potentials of Phosphorus and Potassium (mg/kg) correspond to the ashes of the industries "Arquímides Colina" (380,87 and 2625) and "Bartolomé Masó" (1056,75 and 1500) ) with the lowest content of heavy metals. The use of the ashes in the cultivation of Lactuca sativa L. (Lettuce) in controlled and field conditions; showed a positive effect on the variables of plant growth and agricultural yield. In addition, the ashes replace the losses of the macronutrients; which together with the availability and low cost of the ash allows its use as a natural mineral fertilizer.